The generalization of the Schur multipliers of Bieberbach groups - Masri, Rohaidah (2014)
The Schur multiplier is the second homology group of a group. It has been found to be isomorphic to the kernel of a homomorphism which maps the elements in the exterior square of the group to the elements in its derived subgroup. Meanwhile, a Bieberbach group is a space group which is a discrete cocompact group of isometries of oriented Euclidean space. In this research, the Schur multipliers of Bieberbach groups with cyclic point group of order two of finite dimension are computed.